IMPLEMENTATION OF POPULATION ADMINISTRATION INFORMATION SYSTEM (SIAK) IN TOLOTIO VILLAGE BONEPANTAI SUB-DISTRICT, BONE BOLANGO DISTRICT - Novalia Mohi; Djamila Podungge; Maman Musa (LP2M Universitas Bina Mandiri Gorontalo, 2026)
This study aims to evaluate the implementation of the Population Administration Information System (SIAK) in Tolotio Village, Bonepantai Sub-district, Bone Bolango District. Specifically, it analyzes the operational workflow managed by the Village Registration Officer (PRC), assesses the impact of decentralized online innovations on community accessibility, and identifies the core infrastructure and data-mismatch constraints affecting daily efficiency. This study employs a descriptive qualitative research design with a case study approach. Data were collected through in-depth interviews with key informants including the village operator and village head complemented by field observations and documentation reviews. The results indicate that the integration of SIAK at the village level has successfully shifted the public service paradigm from bureaucratic centralization to grassroots digital integration, utilizing a hybrid workflow that combines smartphone scanning with informal WhatsApp coordination. However, the daily efficiency of the system is heavily bottlenecked by twin operational barriers: external technological failures in the form of centralized network disruptions and deeply rooted internal human errors involving data mismatches between legacy family records and authentic school diplomas. Despite these technical vulnerabilities, the localized system has drastically minimized socio-spatial isolation and transaction costs, providing unprecedented administrative ease for crucial document updates and cross-regional migration processing for the rural coastal community.